2023
DOI: 10.3390/bioengineering10060693
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antibacterial Properties, Surface Morphology and In Vitro Bioactivity of Hydroxyapatite-Zinc Oxide Nanocomposite Coating by Electrophoretic Deposition Technique

Waseem Akram,
Rumaisa Zahid,
Raja Muhammad Usama
et al.

Abstract: To develop medical-grade stainless-steel 316L implants that are biocompatible, non-toxic and antibacterial, such implants need to be coated with biomaterials to meet the current demanding properties of biomedical materials. Hydroxyapatite (HA) is commonly used as a bone implant coating due to its excellent biocompatible properties. Zinc oxide (ZnO) nanoparticles are added to HA to increase its antibacterial and cohesion properties. The specimens were made of a stainless-steel grade 316 substrate coated with HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…MSS was coated with HA-ZnO using ED reported to develop a uniform, corrosion resistant with low toxicity in a study. They also reported it to show antibacterial activity against S. aureus [146]. In a separate study, TiN ion-plated magnetic stainless steel (447J1) using PVD was found to develop durable corrosion resistance [60].…”
Section: Asp N Agmentioning
confidence: 96%
“…MSS was coated with HA-ZnO using ED reported to develop a uniform, corrosion resistant with low toxicity in a study. They also reported it to show antibacterial activity against S. aureus [146]. In a separate study, TiN ion-plated magnetic stainless steel (447J1) using PVD was found to develop durable corrosion resistance [60].…”
Section: Asp N Agmentioning
confidence: 96%